2022
DOI: 10.1155/2022/5791471
|View full text |Cite
|
Sign up to set email alerts
|

ANP32 Family as Diagnostic, Prognostic, and Therapeutic Biomarker Related to Immune Infiltrates in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common tumors worldwide, with high incidence and mortality rate. There is an urgent need to identify effective diagnostic and prognostic biomarkers for HCC. Members of the acidic leucine-rich nucleophosphoprotein 32 (ANP32) family, which mainly includes ANP32A, ANP32B, and ANP32E, are abnormally expressed and have prognostic value in certain cancers. However, the diagnostic, prognostic, and therapeutic value of ANP32 family members in HCC has not yet been fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In addition, we compared the e cacy of multiple machine learning algorithms by C-index to construct the best consensus prognostic model and validated the genes in the model (ANP32B, KIF2C, and RAN) by mIHC. Additionally, Liu et al found that high ANP32B expression correlated with higher pathological stages of HCC, and knockdown of ANP32B would contribute to delay the progression of HCC [33]. A previous study found signi cantly higher expression levels of RAN in HCC tissues, which suggests that high expression of RAN is associated with poor prognosis in HCC [34].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, we compared the e cacy of multiple machine learning algorithms by C-index to construct the best consensus prognostic model and validated the genes in the model (ANP32B, KIF2C, and RAN) by mIHC. Additionally, Liu et al found that high ANP32B expression correlated with higher pathological stages of HCC, and knockdown of ANP32B would contribute to delay the progression of HCC [33]. A previous study found signi cantly higher expression levels of RAN in HCC tissues, which suggests that high expression of RAN is associated with poor prognosis in HCC [34].…”
Section: Discussionmentioning
confidence: 98%
“…Higher ANP32B mRNA expression is a marker of poor prognosis in patients with breast cancer [ 17 ], whereas ANP32B was found to suppress breast cancer tumor growth [ 18 ]. ANP32B mRNA and protein are highly expressed in hepatocellular carcinoma (HCC), with these levels of expression associated with tumor cell proliferation and invasion, suggesting that ANP32B is pro-oncogenic in HCC [ 19 ]. In contrast, ANP32B downregulation was found to have antiapoptotic effects in HCC, whereas ANP32B upregulation did not lead to HCC apoptosis and functioned as a cell cycle progression factor in HCC [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ANP32B protein was found to be located in the nucleus and be associated with brain development by regulating the proliferation of neuronal cells [ 13 ]. ANP32B was shown to be important for cell proliferation, apoptosis, and cell cycle progression [ 14 , 15 ], and to participate in various types of cancer, including leukemia [ 14 , 16 ], breast cancer [ 17 , 18 ], hepatocellular carcinoma [ 19 , 20 ], pancreatic adenocarcinoma [ 21 ] and thyroid carcinoma [ 22 ]. Although ANP32B expression was also found to be upregulated in patients with CRC [ 23 ], the precise function of ANP32B in CRC remains to be determined.…”
Section: Introductionmentioning
confidence: 99%